Peatlands Rehabilitation through Species Enrichment on Post-fire Oil Palm Plantation Area - Rizki Mardhatillah; Prijanto Pamoengkas; Istomo Istomo (Media Konservasi, 2019)
Forest fires and land conversion to oil palm plantations are one of the major threats that caused dangerous impacts on the existence of peatlands in Indonesia. Rehabilitation by plant type enrichment method is an effort that can be developed to restore the ecological and hydrological functions of degraded peatlands. This study aimed to analyze biophysical conditions (soil characteristics), analyze the growth response of plant species against the combination of planting types; analyze the choice of planting combinations that are in accordance with the physical conditions of the field and the needs of local communities. This study was designed by varying the diversity of tree species or combination of planting. The research plot consists of three size area (5m x 5m, 10m x 10m, and 20m x 20m). The species that used in this study consists of Shorea balangeran, Durio zibethinus, Archidendron pauciflorum, Parkia speciosa, Coffea liberica and Areca pinanga. The results showed that the research plot has soil characteristic from mesotropic fertility categories (moderate fertility) to eutophic (fertile), while the pH between 3.2 – 3.5 (very acidic). The growth of plant species at the age of five months has growth rate differentiation both height and diameter in each combination of planting.  The height growth of Shorea balangeran species the highest which average of 35.16 cm while the diameter growth of Areca pinanga is 8.13 mm. The best combination of planting is a combination of six species wich consists Shorea balangeran, Durio zibethinus, Archidendron pauciflorum, Parkia speciosa, Coffea liberica and Areca pinanga. Keywords: enrichment planting, growth, rehabilitation, peatlands